Peran Teknologi dalam Meningkatkan Kesehatan Masyarakat: Evaluasi Model Bisnis Halodoc sebagai Platform Telemedicine: Waluyo Rudiyanto, Anisa Nuraisa Jausal, Nabeel Muhammad, Rasha Andhika Satria, Malik Ahza Nugroho - Waluyo Rudiyanto; Anisa Nuraisa Jausal; Nabeel Muhammad; Rasha Andhika Satria; Malik Ahza Nugroho (Jurnal Kedokteran Universitas Lampung, 2026)
This study aims to evaluate the role of technology in improving public health through Halodoc’s business model as a telemedicine platform in Indonesia, as well as analyze regulatory challenges, data security, and user trust. This research employs a qualitative method with a case study approach and systematic literature analysis. Data were collected through in-depth review of scientific literature, case study implementation of Halodoc, and analysis of telemedicine regulatory policies in Indonesia. The analysis focuses on the impact of telemedicine adoption, platform business models, and implementation challenges during and post-COVID-19 pandemic. Halodoc plays a significant role in expanding access to healthcare services, particularly in urban areas. The platform integrates online medical consultations, digital prescription provision, and medication delivery within an efficient ecosystem. During the COVID-19 pandemic, Indonesian telemedicine users surged from 2 million (2019) to 20 million (2020), demonstrating extraordinary growth. However, research reveals critical challenges including regulatory ambiguity for P2P (provider-to-patient) models, concerns about personal data security, access disparities between urban and rural areas, and limited user trust in online diagnosis without physical examination. Although Halodoc has proven its value proposition in improving healthcare efficiency and accessibility, continuous integration into the national health system requires strengthened comprehensive regulation, standardized data security, and strategic collaboration between public and private sectors. The government needs to develop clear telemedicine policies to maximize the potential of digital platforms in creating an inclusive and sustainable healthcare ecosystem.